APLIKASI PRESENSI GURU BERBASIS WEB DALAM UPAYA PENINGKATAN AKURASI DAN PENCATATAN KEHADIRAN GURU (STUDI KASUS SD NEGERI 213/IX MARKANDING) - Elzas, Elzas; Adriana, Windy; Yudha Prasetyo, Danu (FORTECH (Journal of Information Technology), 2024)
This research aims to develop a web-based teacher attendance application specifically designed for SD Negeri 213/IX Markanding to increase the accuracy and efficiency of recording teacher attendance. When using a manual attendance system, you often encounter various obstacles such as the possibility of recording errors, delays in data processing, and the potential for attendance fraud. This application uses geolocation technology to record teacher attendance accurately and can be accessed via laptop devices. This research uses a qualitative approach with waterfall methodology in system development. This application provides real-time attendance information to teachers and makes it easier to process and report attendance data which can be accessed at any time. Apart from that, this application also facilitates giving awards to outstanding teachers based on accurately recorded attendance data. The introduction of this application at SD Negeri 213/IX Markanding aims to increase the efficiency of attendance management, facilitate school management decision making and support more objective evaluation of teacher performance.